2023
DOI: 10.1021/acs.organomet.3c00060
|View full text |Cite
|
Sign up to set email alerts
|

Improved Trianionic Pincer Ligand Synthesis for Cyclic Polymer Catalysts

Abstract: An easier, safer, and scalable approach to the synthesis of a trianionic pincer ligand and its use in the preparation of the Mo cyclic polymer catalyst [O2C((p-OMe-C6H4)C)Mo(η2-CHC t Bu)(THF)] (7) are reported. The synthesis of the [ t BuOCO]Me2 (1) ligand is simplified to a reaction that allows scaling up, thus reducing the main barrier to accessing cyclic polymer catalysts. The synthesis allows for the derivatization of the C ipso carbon of the central ring of the pincer. Taking advantage of this, a deute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Recently, Grubbs et al reported the silica-supported ruthenium heterogeneous catalyst for the bulk REMP of cyclopentene, allowing catalyst recovery . These catalysts have provided access to cyclic variants of commercially relevant and historically important polymers, such as poly­(propylene), poly­(norbornene), poly­(methyl-1-pentene), poly­(phenylacetylene), and poly­(acetylene) . Interestingly, upon doping, cyclic poly­(acetylene) showed conductivity on the higher end of nonstretch aligned linear poly­(acetylene), and cyclic poly­(methyl-1-pentene) exhibited higher T g compared to its commercial linear counterpart while maintaining remarkable optical clarity. , Veige et al also reported the synthesis of cyclic­(polyacetylene) via REMP of a soluble polymer precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Grubbs et al reported the silica-supported ruthenium heterogeneous catalyst for the bulk REMP of cyclopentene, allowing catalyst recovery . These catalysts have provided access to cyclic variants of commercially relevant and historically important polymers, such as poly­(propylene), poly­(norbornene), poly­(methyl-1-pentene), poly­(phenylacetylene), and poly­(acetylene) . Interestingly, upon doping, cyclic poly­(acetylene) showed conductivity on the higher end of nonstretch aligned linear poly­(acetylene), and cyclic poly­(methyl-1-pentene) exhibited higher T g compared to its commercial linear counterpart while maintaining remarkable optical clarity. , Veige et al also reported the synthesis of cyclic­(polyacetylene) via REMP of a soluble polymer precursor.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been pioneered by Veige and co-workers utilizing a high-valent [W VI ] catalyst and a variety of terminal alkynes. [22][23][24][25][26][27][28][29] Likewise, Maeda and co-workers have also reported cyclic polyalkynes of tolanes invoking Nb, [30] Ta, [31] and W [32] alkyne adducts. More recently, we have identified [V V ] alkylidynes (Scheme 1, A) [33][34] as pre-catalysts for the cyclic polymerization of phenylacetylene (cyclic-PPA, B).…”
mentioning
confidence: 99%
“…Inspired by the growing popularity of ring-opening metathesis polymerization (ROMP) methodologies to synthesize linear macromolecules with complex sequences and rich functionalities, ring-expansion metathesis polymerization (REMP) methodologies aim to expand the scope of analogous cyclic macromolecules and the ease by which they are made. The evolution of organometallic (e.g., Ru, W, Mo) REMP initiators ,, has lagged compared to the advancements made in ROMP initiator development, likely due to the difficulties associated with synthesizing the former and analytical challenges in characterizing , putative cyclic macromolecules.…”
mentioning
confidence: 99%